ANALISIS TIMBAL DAN KADMIUM DALAM AIR BERSIH MENGGUNAKAN GFAAS - Gilang Reynaldy Supriadi Putra (Journal of Innovation Research and Knowledge, 2026)
Abstract: Heavy metal contamination in water is a critical environmental issue due to its potential adverse effects on human health. This study aims to analyze the concentrations of lead (Pb) and cadmium (Cd) in refill drinking water and clean water (PDAM) using Graphite Furnace Atomic Absorption Spectrometry (GFAAS). This method was selected for its high sensitivity in detecting trace-level metals. The analytical procedure involved sample preparation through acidification, filtration, and digestion, followed by calibration curve construction and quantitative analysis using GFAAS. The results demonstrated excellent linearity for Pb and Cd calibration curves, with coefficients of determination (R²) of 0.9958 and 0.9973, respectively. The concentrations of Pb and Cd in all samples were below the method detection limits (<LOD), indicating compliance with applicable water quality standards. Accuracy testing using the spike recovery method yielded acceptable recovery values, confirming the reliability of the analytical method. These findings suggest that the tested water sources are safe from heavy metal contamination and highlight the importance of continuous water quality monitoring to protect public health.